STRATEGI DIFERENSIASI DALAM PENGEMBANGAN MADRASAH INSPIRATIF DI MAN 2 PONOROGO - Halma Zanaratul Ria; Mukhibat Mukhibat (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: This study aims to describe deeply about the low morale of adolescents such as promiscuity, drug abuse, and fighting. Based on these problems, MAN 2 Ponorogo develops madrassas with a vision of RUBI (Religious, Excellent, Cultured, Integrity).This research uses a qualitative approach. Data collection through interviews, observation, and documentation. Data analysis techniques include data reduction, presentation, and verification. The results of this study: (1) The stage of differentiation strategy planning begins with the madrasa head creative thinking that is motivated by learning theory. Next, the vision formulation stage which includes the preparation of RKM, RKTM, and RKATM; (2) The stage of implementing the differentiation strategy includes the implementation of activities in madrasas based on RUBI; (3) Evaluation stage, which includes monitoring and evaluation by the team chosen by the madrasa head, so that results are obtained in the form of obstacles in each aspect of RUBI along with solutions for its resolution. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan secara mendalam tentang rendahnya moral remaja seperti pergaulan bebas, penyalahgunaan narkoba, dan tawuran. Berdasarkan permasalahan tersebut, MAN 2 Ponorogo mengembangkan madrasah dengan visi RUBI (Religius, Unggul, Berbudaya, Integritas). Penelitian ini menggunakan pendekatan kualitatif. Pengumpulan data melalui wawancara, observasi, dan dokumentasi. Teknik analisis data meliputi reduksi, penyajian, dan verifikasi data. Hasil penelitian ini: (1)Tahap perencanaan strategi diferensiasi diawali berpikir kreatif kepala madrasah yang dilatarbelakangi teori pembelajaran. Selanjutnya, tahap perumusan visi yang meliputi penyusunan RKM, RKTM, dan RKATM; (2)Tahap pelaksanaan strategi diferensiasi meliputi implementasi kegiatan di madrasah berdasarkan RUBI; (3)Tahap evaluasi, meliputi monitoring dan evaluasi oleh tim yang dipilih kepala madrasah, sehingga didapatkan hasil berupa kendala pada setiap aspek RUBI beserta solusi penyelesaiannya.